Pengaruh Job Burnout, Role Conflict, dan Abusive Leadership Terhadap Perilaku Karyawan di Bank Swasta - Irfan, Helmy; Rizana, Dani (PT. Karya Inovatif Nusantara, 2024)
This study adopts a quantitative approach to understand the phenomenon of quiet quitting among employees in the banking sector. Present studies directed to understand the linkage between Job burnout, Role conflict and Abusive Leadership toward employee’s quiet quitting. Conducted in January 2024, the research utilized a survey method through the distribution of questionnaires to randomly selected respondents from five banks. A total 75 employees join as participant in the survey. To analyse the data, this study used multiple regression analysis. SPSS version 16 were employed in the analysing process. Findings indicate that Job burnout has a positive effect on employees quiet quitting. Role conflict also showed a significant influence on employee quiet quitting. And the last, Abusive Leadership significantly impact quiet quitting. Job burnout leads to a loss of motivation and interest in work, while Role conflict triggers feelings of pressure and confusion among employees. Abusive Leadership styles create an unfavourable work environment. Understanding these factors is crucial for bank management to devise strategies aimed at mitigating quiet quitting and cultivating a work environment conducive to employee well-being and productivity.